2006
DOI: 10.1111/j.1530-0277.2006.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Alcohol Intake in Humans Attenuates Monocyte Inflammatory Responses: Inhibition of Nuclear Regulatory Factor Kappa B and Induction of Interleukin 10

Abstract: Our findings suggest that acute alcohol consumption has dual anti-inflammatory effects that involve augmentation of IL-10 and attenuation of monocyte inflammatory responses involving inhibition of NF-kappaB. These mechanisms may contribute to the beneficial effects of moderate alcohol use on atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
112
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 25 publications
15
112
4
2
Order By: Relevance
“…In line with this, it has been reported that acute in vitro exposure to ethanol (EtOH) decreases production of inflammatory cytokines (i.e., interleukin [IL] 1, IL6, and tumor necrosis factor a [TNFa]) by human monocytes (4)(5)(6)(7)(8) and macrophages (i.e. TNFa) (9), these effects being mediated through toll-like receptors (TLR) (10).…”
mentioning
confidence: 84%
“…In line with this, it has been reported that acute in vitro exposure to ethanol (EtOH) decreases production of inflammatory cytokines (i.e., interleukin [IL] 1, IL6, and tumor necrosis factor a [TNFa]) by human monocytes (4)(5)(6)(7)(8) and macrophages (i.e. TNFa) (9), these effects being mediated through toll-like receptors (TLR) (10).…”
mentioning
confidence: 84%
“…In vivo the consumption of alcohol in one setting implies that the entire dose of alcohol is consumed at once, while a 'binge' is defined by NIAAA as an excessive pattern of alcohol drinking that produces BAL greater than 0.08% within a 2-h period and may, or may not, be associated with dependence [11,12,17,18] . Thus any model using consumption of biologically active amounts of alcohol within 2 h is considered an acceptable model of AAA [81,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] . (2) Establish an exposure to an accurate concentration of ethanol.…”
Section: Models Of Aaamentioning
confidence: 99%
“…For in vitro studies the 10-100 mmol/L ethanol range is considered physiological, with 25 mmol/L ethanol being close to 0.08% BAL achieved in vivo after 4-5 drink equivalents [7,11,12,[98][99][100][101][102][103][104][105][106] . For the in vivo studies an 0.08% BAL or above this level yields signs of intoxication and it is employed in the majority of biomedical studies [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] . (3) Recruit individuals who are currently not and never have been alcohol abusers for in vivo studies and employ alcohol-naïve primary cells or cell lines for in vitro studies.…”
Section: Models Of Aaamentioning
confidence: 99%
“…In contrast, although the combined stimulation of 25 mM ethylic alcohol and LPS did not significantly changed IL-10 production after 10 h stimulation, 100mM alcohol and LPS significantly decreased monocyte IL-10 production than LPS alone [36]. Several other studies using a completely different protocol including drinking of alcohol in healthy volunteers and blood receipt after 18-24 hours, which was stimulated with or without LPS, found a significant increase in IL-10 production [37][38][39][40]. These findings do not contrast our results since a shorter timeframe was applied in our experiments in addition to the use of whole blood in an ex-vivo environment.…”
Section: Discussionmentioning
confidence: 90%
“…Acute alcohol exposure in vivo and in vitro induced IL-10 production in human monocytes, with or without LPS stimulation [32,[36][37][38][39][40]41], and thus may interfere with the cell-mediated and humoral immunity by both reducing inflammatory cytokine production and preventing T-cell proliferation [17,36,42].…”
Section: Discussionmentioning
confidence: 99%